Pemodelan Spasial Berbasis Cellular Automata untuk Identifikasi Potensi Alih Fungsi Lahan di Kawasan Konservasi Pantai Timur Surabaya - Cahyono Susetyo; Lukman Yusuf; Nursakti Adhi Pratomoatmojo (Jurnal Perencanaan Wilayah, 2019)
Limited vacant land in Surabaya City made one of its conservation area, the eastern coast of Surabaya (Pamurbaya), very attractive to property developers. However, existing spatial plan documents state that this area is inetended as conservation area or urban green space. However, up to 92,66% of this area is owned by individuals, not by the government of Surabaya City. Therefore, there is a possibilty of land use change from conservation to built-up areas. The purpose of this research is to idenfity the land use change potentials in Pamurbaya by using the Cellular Automata-Based Spatial Modelling. The results of the modelling indicates that the dominant factor that influencing the land use change in Pamurbaya is the presence of the Eastern Ring Road of Surabaya City and existing residential areas. The model predicts that beetween 2019-2034, housing in Pamurbaya will grow as much as 62% from the current size of housing land uses. Industrial land use will grow 7%, commercial areas will grow 15%, and conservation/green spaces will reduced by 29% from its current size. Keywords:Landuse Change; Cellular Automata, Land Use Modelling